The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1155/2020/5782485
|View full text |Cite
|
Sign up to set email alerts
|

Açaí (Euterpe oleracea Mart) Consumption and Prevention of Chronic Diseases: Is There an Association? A Preliminary Study

Abstract: Background. Flavonoids from a variety of fruits, including açaí, have beneficial antioxidant activity in several diseases, including cancer. Breast cancer is the second most prevalent cancer among Brazilian women. Studies have shown the action of flavonoids on neoplastic cells, as well as on diabetes and neurodegenerative and cardiovascular diseases. Objective. To analyze the relationship between the consumption of açaí and the presence of chronic diseases in women residing in the rural area of São Luís, Maran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“… In vitro ↓ pro-inflammatory; ↑ anti-inflammatory cytokines; modulation of NLRP3 inflammasome protein expression Machado et al (2019) Fruit pulp Anthocyanins and phenolic compounds Clinical study with forty healthy volunteer women ↑ concentration of apolipoprotein A-I; ↓ radical oxidative stress, ox-LDL and malondialdehyde; ↑ total antioxidant capacity. Pala et al (2018) Fruit pulp Anthocyanins and phenolic compounds Cross-sectional, retrospective, and analytical study Suggests a reduction of occurrence of diabetes and hypertension in women Silva et al (2020) ; Bacaba ( Oenocarpus ssp. ) Fruit powder Total phenolics and anthocyanins In vitro Antioxidant activity Nascimento et al (2019) Fruit pulp oil Total phenolics and PUFAs In vitro Antioxidant activity Pinto et al (2018) Fruit pulp Phenolics and flavonoids In vitro Antioxidant properties Carvalho et al (2016) Fruit pulp extract Phenolic compounds Cell culture of MCF-7 cells and cell proliferation Antiproliferative capacities; induced apoptosis in MCF-7 breast cancer cells through the mitochondrial pathway; highest activation caspase-9.…”
Section: Potential Effects Of Amazonian Fruits and Oilseeds To Streng...mentioning
confidence: 99%
See 1 more Smart Citation
“… In vitro ↓ pro-inflammatory; ↑ anti-inflammatory cytokines; modulation of NLRP3 inflammasome protein expression Machado et al (2019) Fruit pulp Anthocyanins and phenolic compounds Clinical study with forty healthy volunteer women ↑ concentration of apolipoprotein A-I; ↓ radical oxidative stress, ox-LDL and malondialdehyde; ↑ total antioxidant capacity. Pala et al (2018) Fruit pulp Anthocyanins and phenolic compounds Cross-sectional, retrospective, and analytical study Suggests a reduction of occurrence of diabetes and hypertension in women Silva et al (2020) ; Bacaba ( Oenocarpus ssp. ) Fruit powder Total phenolics and anthocyanins In vitro Antioxidant activity Nascimento et al (2019) Fruit pulp oil Total phenolics and PUFAs In vitro Antioxidant activity Pinto et al (2018) Fruit pulp Phenolics and flavonoids In vitro Antioxidant properties Carvalho et al (2016) Fruit pulp extract Phenolic compounds Cell culture of MCF-7 cells and cell proliferation Antiproliferative capacities; induced apoptosis in MCF-7 breast cancer cells through the mitochondrial pathway; highest activation caspase-9.…”
Section: Potential Effects Of Amazonian Fruits and Oilseeds To Streng...mentioning
confidence: 99%
“…They suggested that regular açaí intake can positively influence endogenous antioxidant processes, thereby protecting cells from oxidative damage. Moreover, açaí consumption can affect lipid metabolism, displaying beneficial effects on LDL-c and HDL-c control ( Aliaño-González et al, 2020 , Liz et al, 2020 , Machado et al, 2019 , Magalhães et al, 2020 , Silva et al, 2019 , Silva et al, 2020 , Souza et al, 2020 ). Furthermore, when studying the biological properties of the açaí oil, several researchers found a powerful in vitro antioxidant activity from it as well as a great content of phenolic compounds non-anthocyanins, which could be potentialized when encapsulated into micro- or nanoparticles to a controlled release in specific targets ( Pacheco-Palencia et al, 2008 , Rufino et al, 2011 , Teixeira-Costa et al, 2020 ).…”
Section: Potential Effects Of Amazonian Fruits and Oilseeds To Streng...mentioning
confidence: 99%